2 in 1 (gender identity disorder) - Ali, Syed Masroor (2011)
A person with this disorder often experiences great discomfort regarding his or her actual anatomic gender. People with gender identity disorder may act and present themselves as members of the opposite sex and may express a desire to alter their bodies. The disorder affects an individual's self-image, and can impact the person's mannerisms and behavior. As gender identity develops in children, with sex-role assignment. Sex role-stereotypes are the beliefs, characteristics and behaviors of individual cultures that are considered normal and appropriate for boys and girls to possess. These "norms" are influenced by ones family and friends, the mass-media, and their community. Since many cultures strongly disapprove of cross-gender behavior, it often results in significant problems for affected persons and those in close relationships with them. In many cases, discomfort is also reported as stemming from the feeling that one's body is "wrong" or meant to be different. The need for treatment is emphasized by the high rate of mental health problems, including Depression with higher suicide rate among untreated transsexual people than in the general population. These problems are not usually related to the gender identity issues themselves, but the social and cultural responses to gender-deviated individuals. An example which classically illustrates GENDER IDENTITY DISORDER is the case of a young man from Brunei Darussalam, who was seen and treated. This presentation will highlight the cultural and religious perspective of this Disorder.